Implementasi Quick Response Code Indonesia Standard (QRIS) Dalam Meningkatkan Transaksi Nontunai Pada Generasi Milenial Dibandingkan Dengan Generasi Z : Studi Kasus Pada Nasabah Bank Jateng KCP RSU Wonogiri - Banu Yoga Harsaputra; Susilaningtyas Budiana Kurniawati; Supartini Supartini (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of the implementation of the Quick Response Code Indonesian Standard (QRIS) on the increase of cashless transactions among Millennial and Generation Z customers of Bank Jateng KCP RSU Wonogiri. The research employs a quantitative approach using a survey method through the distribution of questionnaires to respondents categorized as Millennials and Generation Z. Data analysis was conducted using simple linear regression with classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results indicate that the implementation of QRIS has a significant effect on the increase of cashless transactions among both Millennials and Generation Z. These findings suggest that ease of use, perceived benefits, and trust in QRIS encourage a higher frequency of cashless transactions among digital-native generations.